2011
DOI: 10.1007/s12221-011-0857-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemical degradation of thermoplastic polyurethane for recycling polyether polyol

Abstract: Thermoplastic polyurethane, based on 4,4'-diphenylmethane diisocyanate and polyether polyol, was degraded by glycol and ethanolamine at 170 o C. Optimum conditions for the glycolysis of thermoplastic polyurethane were investigated by adjusting the ratio of polymer to degradation reagent, glycol to ethanolamine as well as the reaction temperature. The degradation reaction was conducted under nitrogen atmosphere and accelerated by catalysts such as lithium acetate, which was evidenced by lowering the degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Therefore, the spectroscopy and GPC results confirm the depolymerization mechanism proposed. In fact, Wang et al 33 studied the chemical degradation of PU and from the GPC results detected aromatic compounds derived from initial MDI‐carbamates and amines, proving that the RP contains aromatic byproducts derived from the starting isocyanates, which is in agreement with the results previously discussed. Furthermore, Datta 25 in his studies regarding the depolymerization of PU via glycolysis reported the total decomposition of PU chains yielded the main reactants used to produce the original foams, i.e., polyether polyol.…”
Section: Resultssupporting
confidence: 86%
“…Therefore, the spectroscopy and GPC results confirm the depolymerization mechanism proposed. In fact, Wang et al 33 studied the chemical degradation of PU and from the GPC results detected aromatic compounds derived from initial MDI‐carbamates and amines, proving that the RP contains aromatic byproducts derived from the starting isocyanates, which is in agreement with the results previously discussed. Furthermore, Datta 25 in his studies regarding the depolymerization of PU via glycolysis reported the total decomposition of PU chains yielded the main reactants used to produce the original foams, i.e., polyether polyol.…”
Section: Resultssupporting
confidence: 86%
“…In latest researches, the technological scenario for PU recycling is not changed. Glycolysis is one of the most studied process [12, 13], being applied to flexible [14] and semirigid thermoset foams [15] as well as to thermoplastic PU [16]. Microwave irradiation has been used in combination with glycolysis to improve PU foam recycling [17].…”
Section: Introductionmentioning
confidence: 99%
“…[ 2,7,8 ] For example, hydrolysis of PUs can be employed in certain cases to recover the original alcohol monomer (polyol), along with the amine analogue of the original isocyanate monomer. [ 9–13 ] Similarly, various amines, [ 14–20 ] alcohols, [ 14,15,17–19,21–25 ] and acids [ 5,26–32 ] have been used to displace the carbamate linkage and thereby depolymerize PUs. Generally speaking, however, these depolymerization strategies are energy intensive, requiring high temperature, high pressure, and/or long reaction times, and they are inefficient, requiring stoichiometric quantities of cleavage reagents to yield complex mixtures of monomers and oligomers (i.e., incomplete depolymerization) that must be further separated and purified.…”
Section: Methodsmentioning
confidence: 99%